Hidden burden of osteoporosis in alpha-1 antitrypsin deficiency. (27th June 2018) - Filipas, Emanuela; Southern, Iain; Khanna, Pooja; Banerjee, Ritwik
Abstract : This is a reminder of a rare cause of osteoporosis that remains widely underdiagnosed and lacks specific evidence on its optimal management. We bring a case report of a patient presenting with erectile dysfunction and high testosterone level but also elevated sex-hormone binding globulin hence low free androgen index as well as evidence of organ specific hypogonadal side effects such as osteoporosis. A unifying diagnosis of alpha-1 antitrypsin deficiency (AATD) brought together his coexistent mild chronic obstructive pulmonary disease as well as a new finding of previously unrecognised liver disease. This case highlights the uncertainties over the mechanism of osteoporosis in AATD as well as the controversies over best way to manage it. The efficacy of testosterone replacement in managing osteoporosis in the context of AATD remains untested. National registries for AATD would be best placed at gathering further evidence in this area.